2019
DOI: 10.1088/1742-6596/1293/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent characteristics of neutron signals from a current-biased Nb nanowire detector with 10B converter

Abstract: We are developing a new type of the neutron imager based on a superconducting neutron detector. We previously succeeded in constructing and demonstrating neutron detection capability of a superconducting current-biased kinetic inductance detector (CB-KID). In order to improve the spatial resolution and detection efficiency, the characteristics of a superconducting neutron detector have been studied systematically in the present work. As an extension of studying the characteristics of neutron detector, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The number of events as a function of wavelength measured by using the Y meanderline (figure 7) reproduced well the known profile for neutrons at BL10 of the J-PARC facility [12]. Operating CB-KID at various different temperatures revealed that the number of counting events increased remarkably when the operating temperature increased to near the critical temperature of the meanderline [23]. This suggests that hot-spot sizes become larger than the repetition period of the meanderline at temperatures close to the critical temperature [23].…”
Section: Detection Efficiency Of the Superconducting Neutron Detectorsupporting
confidence: 68%
See 1 more Smart Citation
“…The number of events as a function of wavelength measured by using the Y meanderline (figure 7) reproduced well the known profile for neutrons at BL10 of the J-PARC facility [12]. Operating CB-KID at various different temperatures revealed that the number of counting events increased remarkably when the operating temperature increased to near the critical temperature of the meanderline [23]. This suggests that hot-spot sizes become larger than the repetition period of the meanderline at temperatures close to the critical temperature [23].…”
Section: Detection Efficiency Of the Superconducting Neutron Detectorsupporting
confidence: 68%
“…Operating CB-KID at various different temperatures revealed that the number of counting events increased remarkably when the operating temperature increased to near the critical temperature of the meanderline [23]. This suggests that hot-spot sizes become larger than the repetition period of the meanderline at temperatures close to the critical temperature [23]. We are currently considering how to increase the detection efficiency of simultaneous X and Y measurements of the meanderlines.…”
Section: Detection Efficiency Of the Superconducting Neutron Detectormentioning
confidence: 99%
“…One of the best superconducting neutron sensors was used for this experiment. The characteristics of the sensor were systematically investigated in a previous study [4,6]. The structure of a superconducting neutron sensor consists of a pair of meanderlines (X and Y sensors) [15][16][17] with an orthogonal stacking and a 10 B layer deposited on top of the X and Y meanderlines to convert neutrons into charged particles to make it easier to sense an electroneutral particle.…”
Section: Superconducting Neutron Sensormentioning
confidence: 99%
“…A neutron detector has three important parameters in the application of neutrons in material science, i.e., spatial resolution, neutron detection efficiency, and energy resolution. We first proposed the idea of a superconducting neutron sensor called a current-biased kinetic inductance detector (CB-KID) [3] and recently reported systematic investigations on its characteristics to optimize the operating conditions [4,5]. We can improve the detection efficiency of the detector by increasing the operating temperature of the superconducting detector to a critical temperature [6].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitudes of the simulated detection efficiencies are consequent from the design, geometry, materials and detection principles of CB-KID. The simulated detection efficiencies are upper bounds for the reality, as they did not consider other significant factors for the efficiency such as signal processing electronics, deadtime, heat transfer within CB-KID, bias current, and detector temperature [19]. The maximum calculated detection efficiency for hits on both X and Y meander lines was 11% for a cold 0.00068 eV neutron beam.…”
Section: Detection Efficiencymentioning
confidence: 99%